THE ROLE OF ENVIRONMENTAL KNOWLEDGE AND GREEN ECONOMY PERCEPTIONS ON GREEN ENTREPRENEURSHIP INTERESTS IN ENTREPRENEURS IN THE FOOD AND BEVERAGE (F&B) SECTOR IN BALI - Ni Kd Sioaji Yamawati; I G. A. Intan Saputra Rini; I Gde Agung Wira Pratama (Bajang Institute, 2023)
This research background is based on increasing public awareness of the importance of protecting the environment and moving towards a green economy. This happens because environmental problems are increasingly complex and have an impact on human survival on earth. One way to overcome this problem is by developing green entrepreneurship or environmentally oriented entrepreneurship. Green entrepreneurship can help to build a sustainable economy and minimize negative impacts on the environment. However, the success of developing green entrepreneurship does not only depend on the entrepreneur's ability, but is also influenced by the entrepreneur's environmental knowledge and perception on green economy. This research aims to identify the factors that influence the interest in green entrepreneurship among entrepreneurs in Bali, especially environmental knowledge and perceptions of the green economy in the food and beverage (F&B) industry sector. Where the use of plastic materials in serving food and drinks is still very difficult to avoid. The analysis technique used in this research is Structural Equation Modelling (SEM) with a Partial Least Square (PLS) method approach. From the test results it can be analysed that the existence of environmental knowledge and perceptions of the green economy influence the interest in green entrepreneurship among entrepreneurs operating in the F&B sector in Bali, this is due to an increase of environmental problems in public awareness, making the environment an important factor in making business decisions